La adopción del e-Gobierno en entornos voluntarios - Cayetano Medina Molina; Ramón Rufin Moreno; Manuel Rey Moreno (Investigaciones Europeas de Dirección y Economía de la Empresa (IEDEE), 2013)
– e-Government development requires a good knowledge of both users' expectations and all the factors that may strength users' adoption of the technology. Chan et al. (2010) proposed several variables that could act as antecedents of the Unified Theory of Acceptance and Use of Technology (UTAUT) model's components in the context of compulsory use environments. The present research addresses the validity of such antecedents when one is dealing with a free use environment instead that with a compulsory one. The methodology is based in building up a structural equation model by means of the PLS technique. Our findings show that the expectations about the result to be obtained and the effort expectations held by the user affect significantly the intention of use of the e-Government platform. In turn, the intention of use and the facilitating conditions have an influence on actual use of the platform. Furthermore, we found that convenience, assistance, trust and avoidance of personal interaction play important roles in terms of UTAUT model's antecedents.
Keywords: M15; M31; M58; 330; e-Government; UTAUT; Convenience; Assistance; Trust; Avoidance of personal interaction